The Dynamic of Foreign Visitors in Romania since 1990. Current Challenges of Romanian Tourism - Marius-Cristian Neacsu; Silviu Negut; Gheorghe Vlasceanu (Amfiteatru Economic Journal, 2014)
This study represents a quantitative and qualitative analysis of the Romanian tourism phenomenon that focuses on the current challenges to which it has to adapt in order to become competitive on the European market and to overcome its current stage of subsistence tourism. One of the selected criteria for highlighting the main dysfunctions of the Romanian tourism and that also represents the goal of this research is one of the indicators that quantify the annual flow of international tourists that come to Romania. In Romania's post-communist economic development (a negative evolution, of course), tourism remains a real lever for national and regional economic development that can bring Romania numerous competitive advantages on the European Union market.
Keywords: L83; O18; O52; 330; tourism index; the dynamic of foreign visitors; Romanian tourism